PENERAPAN MODEL PEMBELAJARAN PAIR CHECKS UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI SMA NEGERI 2 PUJUD - Marlina, Mustika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :Research onthe application of Pair Checks model aimsto achieve student’smastery learning on the topic ofthe reaction rateinclassXI Science SMA Negeri2 Pujud. Thisresearchused oneshot-study casedesign. Time of data retrievalfrom the dateNovember 11rd –25rd 2014.The sample was selected from the four existing classes, obtained classXI Science2.Data analysis technique used the percentage calculation of mastery learning classical. Based on theresults of data processing obtained mastery learning classical of knowledge competency is 80%, attitude competency is 100% and skill competency is 100%,means that the application of Pair Checks model can achieve student’s mastery learning on the topic ofthe chemical equilibrium in class XI Science SMA Negeri 2 Pujud.Keywords: Pair Checks,Mastery Learning,Chemical Equilibrium